Applying the three-stage SBM-DEA model to evaluate energy efficiency and impact factors in RCEP countries - Zhang, Caiqing; Chen, Panyu (Energy (Oxford), 2022)
Improving regional energy efficiency is the key to solving global energy problems. Regional Comprehensive Economic Partnership (RCEP), as the world's largest free trade zone, energy cooperation is an integral part of the agreement. This paper uses the three-stage SBM-DEA model to analyze the energy efficiency and influencing factors of 13 RCEP countries from 2000 to 2015. The results show that, first, the overall energy efficiency of RCEP is poor at 0.384, with China and Japan having relatively high energy efficiency and Brunei and Cambodia having the worst energy efficiency. The average energy efficiency of developed countries is greater than that of developing countries. Second, optimizing the industrial structure and energy consumption structure can improve energy efficiency. Merchandise trade and government efficiency also have a positive impact on energy efficiency. The development of the tourism industry has unexpectedly reduced energy efficiency. Third, external environmental factors affect energy efficiency differently in each country. Except for China, Japan, and Korea, external environmental factors can lead to overestimating energy efficiency in other countries in RCEP. Finally, some suggestions are put forward to improve the RCEP's energy efficiency. The research results are helpful to understand the changing trend and influencing factors of RCEP's energy efficiency and can provide a reference for international energy cooperation, which is of great practical significance. [Display omitted] •Energy efficiencies of 13 RCEP countries are quantified from 2000 to 2015.•The energy efficiency obtained by the three-stage SBM-DEA model is more accurate.•External influence factors of energy efficiency are studied.•External environment and random errors can lead to overestimation of energy efficiency.